A comparative study of the morphology and molecular biology between the Schneiderian membrane and palatine mucoperiosteum. (December 2022) - Ren, Jing; Geng, Ningbo; Xia, Yixin; Zhou, Yutao; Tan, Jizou; Peng, Wei; Chen, Songling
Abstract: Schneiderian membrane is an indispensable structure for osteogenesis under the sinus floor space after maxillary sinus floor elevation.Therefore, this study aimed to compare the Schneiderian membrane and palatine mucoperiosteum in various aspects to explore whether the Schneiderian membrane has a periosteal layer and osteogenic ability. Schneiderian membrane and palatine mucoperiosteum specimens were collected and stained with HE, Masson, and Sirius red. Immunofluorescence staining was used to observe the expression and localization of mesenchymal stem cells (MSCs). Then MSCs from two tissues were isolated, cultured, and identified. The expression of osteogenic markers OCN, RUNX2, and BMP2 ware detected by Western blotting and quantitative PCR after osteogenic differentiation.The morphological observations revealed both the Schneiderian membrane and palatine mucoperiosteum were composed of three layers.Immunofluorescence staining showed that the inner bone surface layer of the Schneiderian membrane was rich in MSCs, which was similar to the cambium layer of the palatine mucoperiosteum.In addition, MSCs from two tissues showed similar morphological phenotype. After further osteogenic induction of the two groups, the expression of BMP2, RUNX2, and OCN were significantly increased. This study provide a novel insight into that Schneiderian membrane is a mucoperiosteal membrane rich of MSCs, containing a periosteal layer and osteogenic ability similar to mucoperiosteum. Highlights: Schneiderian membrane is a mucoperiosteum with MSCs (Allen and Burr, 2005 ), and containing a periosteal layer similar to the cambium layer of the palatine mucoperiosteum. MSMSCs and PMSCs were consistent with the morphological characteristics and showed similar expression patterns. MSMSCs and PMSCs are of osteoprogenitor origin and the overall osteogenic differentiation potential of MSMSCs was no lower than that of PMSCs.